The pharmaceutical care bundle: development and evaluation of an instrument for inpatient monitoring - Martinbiancho, Jacqueline Kohut; da Silva, Daiandy; Negretto, Giovanna Webster; Gonzatti, Janaína Rodrigues Chagas; Zuckermann, Joice; Winter, Juliana da Silva; Gioda, Ricardo Soares; Rocha, Bruno Simas da (Clinical and Biomedical Research, 2021)
Introduction: Care bundles help healthcare professionals provide the best care possible in a structured and reliable way. The purpose of this study was to develop and apply an instrument for inpatient follow-up by clinical pharmacists, and evaluate its results in a general hospital. Methods: The care bundle was based on previously validated instruments. The population consisted of patients being monitored by clinical pharmacists at a general hospital. The study was conducted in two phases: the first involved the development and implementation of the bundle, and the evaluation of pharmaceutical interventions; the second involved analyzing data from patients treated with the bundle over the course of one year. Results: The bundle included fourteen pharmaceutical follow-up criteria used in different patterns by each area of care. In the first phase of the study, 3263 patients were monitored and 536 pharmaceutical interventions were performed, with an 85.3% compliance rate. Medication review was associated with the highest percentage of pharmaceutical interventions (53.4%), followed by medication reconciliation (16.8%). In the second phase of the study, follow-up data was collected from 21,214 patients. The bundle criteria were used in a similar way in the treatment of clinical, surgical and cancer patients with pharmacotherapy review identified as the most prevalent intervention in all cases (60.1%). Hospital discharge planning and medication reconciliation were performed with a similar frequency in clinical, surgical, pediatric and general patients. Conclusions: The development and validation of a bundle aimed at guiding the clinical activities of pharmacists helped standardize procedures and interventions. Pharmacotherapy review was the bundle criterion with the highest rate of application and interventions due to the hospital’s complexity and the need to consider individual patient needs and follow institutional policies.